Tomato SlDREB gene restricts leaf expansion and internode elongation by downregulating key genes for gibberellin biosynthesis - Li, Jinhua (Journal of experimental botany, 2012)
Plants have evolved and adapted to different environments. Dwarfism is an adaptive trait of plants that helps them avoid high-energy costs under unfavourable conditions. The role of gibberellin (GA) in plant development has been well established. Several plant dehydration-responsive element-binding proteins (DREBs) have been identified and reported to be induced under abiotic and biotic stress conditions. A tomato DREB gene named SlDREB, which is a transcription factor and was cloned from cultivated tomato M82, was found to play a negative role in tomato plant architecture and enhances drought tolerance. Tissue expression profiles indicated that SlDREB was expressed mainly in the stem and leaf and could be induced by abscisic acid (ABA) but suppressed by GA and ethylene. SlDREB altered plant morphology by restricting leaf expansion and internode elongation when overexpressed, and the resulting dwarfism of tomato plants could be recovered by application of exogenous gibberellic acid (GA(3)). Transcriptional analysis of transgenic plants revealed that overexpression of SlDREB caused the dwarf phenotype by downregulating key genes involved in GA biosynthesis such as ent-copalyl diphosphate synthase (SlCPS) and GA 20-oxidases (SlGA20ox1, -2, and -4), thereby decreasing endogenous GA levels in transgenic plants. A yeast activity assay demonstrated that SlDREB specifically bound to dehydration-responsive element/C-repeat (DRE/CRT) elements of the SlCPS promoter region. Taken together, these data demonstrated that SlDREB can downregulate the expression of key genes required for GA biosynthesis and that it acts as a positive regulator in drought stress responses by restricting leaf expansion and internode elongation